Operating in neutral [digital music legislation]. - Perry, T.S.
The law suit against Napster Inc. may affect the development of peer-to-peer technology for years to come. In this paper, the author describes how, playing a pivotal role in the case is electrical engineer A.J. Nichols: appointed by the court as a neutral expert, he is the judge's sole nonpartisan advisor on the technical questions raised
Keywords: A.J. Nichols; Napster; Digital music legislation; Electrical engineer; Judicial advice; Neutral expert